2021
DOI: 10.1002/jsp2.1164
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized histopathology scoring system using machine learning algorithms for intervertebral disc degeneration in the mouse model—An ORS spine section initiative

Abstract: Mice have been increasingly used as preclinical model to elucidate mechanisms and test therapeutics for treating intervertebral disc degeneration (IDD). Several intervertebral disc (IVD) histological scoring systems have been proposed, but none exists that reliably quantitate mouse disc pathologies. Here, we report a new robust quantitative mouse IVD histopathological scoring system developed by building consensus from the spine community analyses of previous scoring systems and features noted on different mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 53 publications
(131 reference statements)
0
43
0
Order By: Relevance
“…Although LSI model developed more calcification in the lower EP, with oral administration of PNS, especially with medium dose (PNS‐M, 80 mg/kg/d), porosity of the EP and formation of bone marrow cavities in sclerotic EP were reduced significantly (Figure 4B‐E ). In line with a quantitative mouse IVD histopathological scoring system previously described to evaluate the whole degenerative IVD, 29 we scored the NP, AF, EP, and AF/NP/EP boundary regions in every single IVD of each group. The combined IVD score showed that all of the LSI operation groups had a significant higher score than the sham operation group, while the PNS‐M‐treated group scored slightly lower than the LSI group (Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LSI model developed more calcification in the lower EP, with oral administration of PNS, especially with medium dose (PNS‐M, 80 mg/kg/d), porosity of the EP and formation of bone marrow cavities in sclerotic EP were reduced significantly (Figure 4B‐E ). In line with a quantitative mouse IVD histopathological scoring system previously described to evaluate the whole degenerative IVD, 29 we scored the NP, AF, EP, and AF/NP/EP boundary regions in every single IVD of each group. The combined IVD score showed that all of the LSI operation groups had a significant higher score than the sham operation group, while the PNS‐M‐treated group scored slightly lower than the LSI group (Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…And then, we applied a quantitative mouse IVD histopathological scoring system to evaluate the IDD from Safranin O‐Fast Green sections. 29 The scoring system analyzed 14 key histopathological features from NP, AF, EP, and AF/NP/EP interface regions. The total score ranges from 0 to 36, classifying normal (0‐6), mild (7‐13), moderate (14‐25), and severe IDD (26‐35).…”
Section: Methodsmentioning
confidence: 99%
“…This review focuses on the nucleus pulposus cells of the human IVD. For representative examples of the other species used in disc (patho)biology the reader is referred to the recent series of a multi-species histopathological grading schemes reported for mice ( Melgoza et al, 2021 ), rats ( Lai et al, 2021 ), rabbits ( Gullbrand et al, 2021 ), large animal ( Lee et al, 2021 ), and human ( Le Maitre et al, 2021 ) discs.…”
Section: The Intervertebral Discmentioning
confidence: 99%
“…This review focuses on the nucleus pulposus cells of the human IVD. For representative examples of the other species used in disc (patho)biology the reader is referred to the recent series of a multi-species histopathological grading schemes reported for mice (Melgoza et al, 2021), rats (Lai et al, 2021), rabbits (Gullbrand et al, 2021), large animal (Lee et al, 2021) the role of genetics and specific genes in NCs towards NPC transition, as well as the use of live-cell imaging technology to monitor this transition (Joo Han . These fundamental and mechanistic studies involving mice will not only shed light on NC (patho)physiology but will also assist in further identifying and confirming cell markers for the specific life-stages of NCs; its journey from the notochord to the disc and its role during maturation and ageing.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Assessment of IVD degeneration: Histological classification system recently developed by Melgoza et al in 2021 was used to quantify the degeneration of the injured level (L6/S1) which allows the independent evaluation of the nucleus pulposus, annulus fibrosus, endplates and interface boundaries 19 .…”
Section: Measuring Thickness Of Af and The Depth Of Partial-width Injurymentioning
confidence: 99%